2017
DOI: 10.1080/15504263.2017.1296603
|View full text |Cite
|
Sign up to set email alerts
|

Correlates of Current Smoking Among Adults Served by the Public Mental Health System

Abstract: Given the high degree of comorbidity of smoking, alcohol disorders, and drug use disorders, the authors highlight the need for integrated interventions that address these issues simultaneously.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
6
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 41 publications
2
6
0
Order By: Relevance
“…The overall smoking prevalence in this study was reported as 72%, which, while alarming, is consistent with the high prevalence of smoking reported among individuals with a mental illness (Chesher et al, 2012;Dickerson et al, 2018;Glasheen, Hedden, Forman-Hoffman, & Colpe, 2014;Grant, Hasin, Chou, Stinson, & Dawson, 2004;Harris, Parle, & Gagné, 2007;Jamal et al, 2016;Lasser et al, 2000;Swarbrick et al, 2017) and in large U.S. national samples of homeless adults (Baggett & Rigotti, 2010;Connor, Cook, Herbert, Neal, & Williams, 2002). The level of nicotine dependence in this sample was high, with a mean FTND score of 6.0 (SD ϭ 2.29).…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…The overall smoking prevalence in this study was reported as 72%, which, while alarming, is consistent with the high prevalence of smoking reported among individuals with a mental illness (Chesher et al, 2012;Dickerson et al, 2018;Glasheen, Hedden, Forman-Hoffman, & Colpe, 2014;Grant, Hasin, Chou, Stinson, & Dawson, 2004;Harris, Parle, & Gagné, 2007;Jamal et al, 2016;Lasser et al, 2000;Swarbrick et al, 2017) and in large U.S. national samples of homeless adults (Baggett & Rigotti, 2010;Connor, Cook, Herbert, Neal, & Williams, 2002). The level of nicotine dependence in this sample was high, with a mean FTND score of 6.0 (SD ϭ 2.29).…”
Section: Discussionsupporting
confidence: 86%
“…While the level of tobacco use in the general population has decreased greatly (Jamal et al, 2016; Reid, Hammond, Rynard, Madill, & Burkhalter, 2017), prevalence rates of smoking for individuals with serious mental illness range from 28% to 80% depending on the overall demographic and clinical profile of the population that is being surveyed (Chesher et al, 2012; Dickerson et al, 2018; Swarbrick et al, 2017). The estimated prevalence of smoking in a national survey of homeless programs was reported to be 75% (Baggett & Rigotti, 2010).…”
mentioning
confidence: 99%
“…The 2009 Health Center Patient Survey similarly found that 56% of adults with severe mental illness as defined by a Kessler 6 score of ≥ 13 reported current smoking, 18 and overall, these prevalence rates are consistent with those from other nationally representative 12 and non-nationally representative samples of adults with SMI. 8,37 Despite these higher smoking rates and the lower quit ratio among individuals with SMI compared to those without SMI, over half of smokers with SMI reported trying to quit in the past year. Thus, a major challenge remains in how to translate motivations to quit into cessation among smokers with SMI.…”
Section: Discussionmentioning
confidence: 99%
“…Before the pandemic, their mortality rates were two to three times higher than the general population [ 15–17 ] and had been increasing over time [ 18 , 19 ]. Studies show that around 60% of this premature mortality is due to preventable and treatable factors, including chronic illnesses, such as diabetes and heart disease [ 20 ], side effects of psychotropic medications [ 21 ], poor diet and sedentary lifestyles [ 22 , 23 ], high rates of smoking [ 24–26 ], lack of health screening and follow-up care [ 27 ], poor quality health care [ 21 ], and service access barriers, such as lack of transportation [ 28 ]. Additionally, people with mental health disorders are at increased risk of infections and are more likely to develop severe organ dysfunction and to die in ICUs than people without these disorders [ 29 ].…”
Section: Introductionmentioning
confidence: 99%